STATES’ SOVEREIGNTY AND THE ENFORCEMENT OF CORE LABOUR RIGHTS OF MIGRANT WORKERS: AN AVOIDABLE CONTRADICTION IN SOME SELECTED MEMBER STATES OF THE ILO AND UN - Irene Fokum Sama-Lang; Akamin Asonga Patrick (American Journals Publishing, 2022)
This paper examines the protection of the core labour rights of migrant workers in some selected Members States of the ILO and UN, and opines that it is only through the protection of the core labour rights of migrant workers that their other work related rights can be conserved. In so doing, it conceptualized the terms ‘core labour rights’ and ‘migrant workers,’ and analyzed their protection under relevant UN and ILO instruments. It examines the notion of States’ sovereignty and the conservation of core labour rights of migrant workers under international law vis- a- vis the practice in some Member States of the UN and the ILO,  and argues that though most Member States have committed themselves to the protection of  core labour rights of migrant workers  by ratifying relevant international instruments, practice shows that they continue to subject the enforcement of core labour rights of migrant workers to their sovereignty. In this light, these researchers generally argue that subjecting the enforcement of core labour rights of migrant workers to the ambit of States’ sovereignty is an avoidable contradiction that can be curbed. To this effect, Member States must review their commitment to the enforcement of the rights of migrant workers, and stand by their obligations in international law or decides whether to subject the enforcement of the rights of migrant workers to their sovereignty by denouncing the relevant international instruments on this subject.
Keywords: States’ Sovereignty; Enforcement; Labour Rights